2020
DOI: 10.1371/journal.pone.0238779
|View full text |Cite
|
Sign up to set email alerts
|

Parents and teachers of children in special education settings value in-school eyecare and written reports of visual status

Abstract: Objectives To evaluate parent and teacher opinion of the provision of in-school eyecare and jargon-free written reporting of visual status for children in special educational settings. Participants and methods A nationally-agreed, in-school eyecare framework for children attending special schools which recommends a full eye examination, dispensing of spectacles and provision of a jargon-free written report of visual outcomes to parents and teachers, was provided to 200 children (mean age 10 years, 9 months; 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…According research conducted by (McConnell et al, 2020) concluded that teacher and parents should make good collaboration in parepared child education. Parents active involve in school program supports child studing and support by learimg at home.…”
Section: Understanding Of Ecementioning
confidence: 99%
“…According research conducted by (McConnell et al, 2020) concluded that teacher and parents should make good collaboration in parepared child education. Parents active involve in school program supports child studing and support by learimg at home.…”
Section: Understanding Of Ecementioning
confidence: 99%
“…Parents commonly cite a lack of support, signposting and information at diagnosis as a key barrier to them accessing services to support their children [11,47]. Whilst each individual child will need a bespoke support package, simple adaptations to educational materials (such as enlarged font and/or fewer items per page) and environments (such as reducing clutter and/or considering area of best visual attention) help a lot of children [48].…”
Section: Management Of Children With CVImentioning
confidence: 99%
“…It is important that eye health professionals provide accessible and meaningful information about the child’s visual strengths and weaknesses to education teams to facilitate provision of support [ 6 , 11 , 14 , 22 , 43 , 47 , 49 , 50 ]. Inclusion of any visual impairment within a child’s Education Health and Care Plan (EHCP) or equivalent is crucial but often overlooked.…”
Section: Introductionmentioning
confidence: 99%